2009
DOI: 10.3844/ajas.2009.463.470
|View full text |Cite
|
Sign up to set email alerts
|

How Does The Bone Shaft Geometry Affect its Bending Properties?

Abstract: Abstract:In this research, ten fresh specimens of sheep tibiae were provided from slaughtered animals. Whole bone specimens were loaded in three-point bending according to standard wet bone test protocols. Mechanical properties were determined and compared with the results which were obtained from two dry bone tests. The results showed that fracture bending moment and bone extrinsic stiffness had significant relations with fracture cross-section dependent parameters (i.e., cross-section area and area moment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Based on the beam theory, the resulting stresses depend on the CSA perpendicular to the load when a load is applied axially to a beam. A smaller CSA produces higher stresses for the same applied force [35,40]. The study found that toy poodles CSA of the radius consistently exhibited reduced dimensions compared to those observed in dachshunds (Table 2), indicating their increased risk of fractures due to higher bone stress levels during loading conditions.…”
Section: Discussionmentioning
confidence: 74%
“…Based on the beam theory, the resulting stresses depend on the CSA perpendicular to the load when a load is applied axially to a beam. A smaller CSA produces higher stresses for the same applied force [35,40]. The study found that toy poodles CSA of the radius consistently exhibited reduced dimensions compared to those observed in dachshunds (Table 2), indicating their increased risk of fractures due to higher bone stress levels during loading conditions.…”
Section: Discussionmentioning
confidence: 74%
“…The area moment of inertia for tubular structures is higher and hence can result in the prediction of lower bending strength. 47 Nevertheless, this method is good for a first approximation. As reported by Motoshima, the bending modulus of humerus, ulna, and radius bones was 10, 15.39, and 15.88 GPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Research groups have experimented on the fracture toughness both on sectioned-bone samples 25,26,53,54 as well as on whole-bone samples. 43,47,55 In the case of the characterization of human elbows for fracture toughness, whole-bone samples have not been reported yet. Research groups have used various ASTM standards for mechanical testing of bones such as D-790 for bending, 56 C-469 and D-1621 for compression testing, 44,57 and E-399 and E-1820 18,30,53,58 for fracture toughness.…”
Section: Resultsmentioning
confidence: 99%